Assessment of myofascial pain syndrome among married female healthcare workers: a cross sectional comparative study in a tertiary care centre - George, James C.; Babu, Subin; Mathew, Deny; Raj, Rejul K.; Kurian, Henry Z.; Abraham, Koshy; Joseph, Kevin; Eapen, Rahul George; Saju, George (International Journal of Research in Orthopaedics, 2023)
Background: Myofascial pain syndrome (MPS) is common among females between ages 20-40 years. Psychosomatic and mechanical reasons are attributed as causative factors. Female health care workers (FHW) in hospitals with rapid patient turn over are vulnerable to develop MPS. Our aim was to ascertain the prevalence of MPS in married FHW working in various departments of the hospital and its association with poor sleep and work stress. Methods: We selected married FHWs in 20-50 years age group and divided them into two groups, medical and paramedical (those involved directly and indirectly with patient care respectively). MPS was diagnosed after detailed personal interview and clinical examination. Sleep duration was divided into less than 5 hours and more than 5hours. Presence of work-related stress and other medical parameters were also recorded. Results: A total of 150 medical and 150 paramedical FHWs were included in the study. Overall prevalence of MPS among FHWs was 42%, of which, medical group was 32% and paramedical was 52%. The paramedical group showed significantly higher prevalence of MPS (p: 0.02). Sleep was less than 5 hours in 29.3% of medical FHW and 13.3% of paramedical. This difference didn’t show any association to MPS (p=0.8). 38% FHW perceived excessive work stress, 40% were paramedical and 36% were medical. This didn’t correlate with prevalence of MPS (p=0.2) among them. Conclusions: Paramedical FHW experienced more MPS than medical and it was more of mechanical type and not due to work stress or sleep deprivation.